Evaluasi Dampak Pemotongan Lereng dan Pengurukan Kembali untuk Pembuatan Lahan Kaveling Perumahan: Studi Kasus di Kecamatan Imogiri, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta: Impact Evaluation of Cutting Slopes and Backfilling for Development of Residential Plots: A Case Study in Imogiri Sub-district, Bantul District, Yogyakarta Special Province - Lisan, Ahmad Rif'an Khoirul; Jamaluddin, Jamaluddin (Jurnal Ecosolum, 2023)
Cutting slopes and backfilling land to make land plots for housing is a common practice in Indonesia.This study aims to identify the impact of cutting slopes and backfilling for the construction of residential plots in Imogiri Subdistrict, Bantul Regency, Yogyakarta Special Province. The study employed a field survey at the study site determined by purposive sampling method to find and evaluate the existing condition. Data was also obtained from literature studies and interviews with local communities. Data analysis was carried out in a spatial qualitative descriptive manner, using a geographic information system approach, with the help of ArcGIS 10.8 Software. The results showed that cutting slopes and backfilling have negatively impacted the environment and local communities. In the backfill process, it is necessary to strengthen the supporting slopes of the piled-up soil, control the water content and compact the soil properly to maintain slope stability and prevent a decrease in soil volume. In addition, it is necessary to periodically monitor the condition of the slopes and the surrounding environment to avoid the possibility of other negative impacts.